Morphological features of ore reserves of the Novo-Uchaly vms deposit (Southern Urals) - A. V. Spirina; V. V. Makarov; I. B. Moiseev; I. V. Vikentyev (Известия высших учебных заведений: Геология и разведка)
Background. The Novo-Uchaly copper-zinc VMS deposit in the Southern Urals (54°10΄54˝N and 59°20΄45˝E) is represented by a steeply dipping lens of Eifelian volcanics (rhyodacites and basalts), which are crumpled into a strongly compressed anticlinal fold. The ore deposit is blind and localised at the convergence of felsic (bottom) and mafic (top) rocks. The deposit is located at depths of 550 m (in the northern part) and 1050 m (in the southern part). The deposit thickness reaches 186 m. The length along the strike and along the dip equals 1250 m and 900 m, respectively. The ore body is intruded by gabbro-diorite and gabbro-diabase dikes. The main ore minerals are pyrite, sphalerite and chalcopyrite, as well as non-metallic minerals, such as quartz, barite and calcite. Unlike most of the Ural VMS deposits, this deposit is the zinc subtype (Zn >> Cu). The ores are predominantly massive and solid sulphide, being banded or brecciated in some parts. The main elements extracted are copper, zinc and sulphur, but gold, silver, cadmium, indium, cobalt, nickel, selenium and tellurium are also obtained.Aim. To clarify the morphology of the ore deposit, to study the ore mineral composition of the upper horizons of its northern part and to determine the underlying reasons for the complex lenticular structure of the sulphide reserve.Materials and methods. In the period 2017—2019, employees of the Institute of Ore Deposits, Petrography, Mineralogy and Biochemistry of the Russian Academy of Sciences (IGEM RAS) together with geologists of the Uchaly Mining and Processing Plant carried out a geological and mineralogical mapping of the deposit in the course of exploration works.Results. The ore contours and mineral composition of the northern part of the ore body were significantly clarified. A series of dikes of variable morphology was identified. A comparison was made of the results with current theories about the structure of the ore deposit. Detailed geological sections were determined and illustrate the complex lenticular structure of the ore deposit complicated by pinch and swell areas. The deposit was formed by processes of dynamic metamorphism.Conclusion. The geological and mineralogical structure of the deposit determined in the study enabled us to propose a schematic reconstruction of the conditions leading to the formation of its folded structure. The findings will help to re-assess the reserves and improve the system of operational exploration and delineation.